THE EFFECT OF 0.12% CHLORHEXIDINE DIGLUCONATE AND 0.1% CHLORINE DIOXIDE ON DISCOLORATION OF NANOFILLED COMPOSITE RESIN - Shabika Shabika; Gustantyo Wahyu Wibowo; Ratna Damma Purnawati; Isniya Nosartika (Jurnal Kedokteran Diponegoro, 2021)
ABSTRAK